Psoriasis and the liver: problems, causes and course - SEÇKİN GENÇOSMANOĞLU, DİLEK; ERGUN, SAFİYE ATLAS TÜLİN; ÖZGEN, ZÜLEYHA (WILEY, 2017)
Background/ObjectivesPsoriasis patients have a higher risk of liver abnormalities such as non-alcoholic fatty liver disease (NAFLD), drug-induced hepatitis, alcoholic hepatitis and neutrophilic cholangitis, than the general population. Associated liver disease limits therapeutic options and necessitates careful monitoring. The aim of the study was to identify liver problems in psoriasis patients and to investigate the underlying causes as well as their course. MethodsThe files of 518 psoriasis patients were retrospectively reviewed. Among these, 393 patients with relevant laboratory data were analysed for liver enzymes and their relation to the known risk factors for liver disease (obesity, diabetes mellitus, alcohol consumption, hepatotoxic medications, dyslipidemia, psoriatic arthritis and infectious hepatitis). ResultsAmong 393 patients, 24% and 0.8% developed liver enzyme abnormalities and cirrhosis, respectively. The most common factors associated with pathological liver enzymes were drugs (57%) and NAFLD (22%). Other rare causes were alcoholic hepatitis, viral hepatitis, neutrophilic cholangitis, autoimmune hepatitis and toxic hepatitis due to herbal therapy. Drug-induced liver enzyme abnormalities were reversible whereas in patients with NAFLD transaminases tended to fluctuate. One patient with herbal medicine-related cirrhosis died of sepsis. ConclusionLiver enzyme abnormalities are common in psoriasis patients and are mostly associated with drugs and NAFLD. Although most cases can be managed by avoiding hepatotoxic medications and close follow up, severe consequences like cirrhosis may develop.
Keywords: drug-induced hepatitis; hepatotoxicity; non-alcoholic fatty liver; psoriasis; GENERALIZED PUSTULAR PSORIASIS; MONITORING PATIENTS; ACUTE HEPATITIS; SKIN-DISEASE; LONG-TERM; METHOTREXATE; FIBROSIS; MANAGEMENT; ARTHRITIS; PROCOLLAGEN